(untitled) (Triyuga Academic Journal, 2024)
This study examined the relationship between consumer attitudes and purchase intentions toward organic products in Kritipur, Kathmandu. Using a 5-point Likert scale survey, data from 57 respondents were analyzed through correlation and regression techniques. The results reveal a considerable positive impact of consumer attitudes, specifically health concerns and environmental care, on purchase intention, with an unstandardized coefficient of 0.854 (p < .001). Consumer attitudes explained 64.7% of the variance in purchase intention, confirming the critical role of favorable attitudes in promoting organic product purchases. However, contrary to the hypothesis, subjective norms had a negative influence on purchase intention (β = -0.261, p = .004), indicating that social pressures may decrease consumer willingness to buy organic products. The findings suggest that marketers should focus on increasing consumers’ trust in organic products and emphasize the health and environmental benefits to increase sales. This study expands existing theoretical models by incorporating health concerns and environmental care as crucial factors influencing consumer attitudes towards organic food.